2001
DOI: 10.1159/000047061
|View full text |Cite
|
Sign up to set email alerts
|

Single Breath Analysis of Endogenous Nitric Oxide in the Newborn

Abstract: Nitric oxide (NO) is found in the exhaled gas of humans immediately after birth. However, variations of endogenous NO concentration during the breathing cycle have not been studied in newborns. We examined 24 newborns without acute respiratory compromise during spontaneous nasal breathing. Gas was sampled from the tip of a thin nasal catheter placed in the hypopharynx. Endogenous NO concentrations measured by chemiluminescence were assigned to the breathing cycle using synchronized CO2 recording. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…In our study, expired NO concentrations in term and preterm infants were lower than those reported for adults and older children according to published data [2,13,14,18,19,24]. Term infants excrete a greater amount of NO in the upper airways in the first hours of life compared to later sampling times, suggesting a role of NO in early postnatal respiratory adaptation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, expired NO concentrations in term and preterm infants were lower than those reported for adults and older children according to published data [2,13,14,18,19,24]. Term infants excrete a greater amount of NO in the upper airways in the first hours of life compared to later sampling times, suggesting a role of NO in early postnatal respiratory adaptation.…”
Section: Discussionsupporting
confidence: 58%
“…The paranasal sinuses are only partially pneumatized in the newborns so that NO might be lower than in older subjects [13]; nevertheless autoinhalation of NO produced in upper airways seems to play a role in the adaptation of the respiratory system to postnatal life [14][15][16][17]. Few studies have evaluated endogenous NO production in the airways of newborns and its role in physiological and pathological circumstances [4,13,18,19]. The aim of this study was to measure the exhaled NO (eNO) in the respiratory system of healthy newborn infants according to their gestational and postnatal age.…”
Section: Introductionmentioning
confidence: 99%
“…This would also imply that our study underestimates any differences between groups. However, it has been shown that both nasal and oral NO levels reflect mixed exhaled NO in infants (28) and techniques to avoid nasal contamination of exhaled air in infants require complicated and demanding equipment, unlikely to become useful in practice (30,31). Also, standardization for expiratory flow in infants is technically possible, but difficult (20), and may be unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…In newborns, paranasal sinuses are not yet developed. However, the nose is also the primary NO source in newborns, with low levels of NO coming from the lower respiratory tract [55].…”
Section: Nasal Nitric Oxide Productionmentioning
confidence: 99%
“…Both on-line and off-line methods have been applied in infants and neonates without the use of sedatives [55,73,81].…”
Section: Tidal Breathing Techniquesmentioning
confidence: 99%